Penampilan fenotipik, parameter genetik karakter hasil dan komponen hasil tanaman melon (Cucumis melo) - Zulfikri Zulfikri; Erita Hayati; M. Nasir (Jurnal Floratek, 2015)
Phenotypic Appearance, Genetic Parameters for Yield Character and Yield Component of Melon (Cucumis melo)ABSTRACT. This study aims to identify the magnitude of predictive value in population genetic parameters melon genotypes . The design used in this study is a randomized block design pattern of non- factorial with 3 replications consisting of 6 treatments genotype extent that Sky Rocket , Action , Amanta , Glamour , Red Aroma , and Apollo , thus there are 18 experimentals. Observed were fruit length , fruit diameter , the largest fruit weight, the smallest fruit weight , fruit weight, and fresh fruit weight / hectare . The results showed that the genotype Glamour shows the best result of the appearance of the character fruit diameter , the smallest fruit weight , fruit weight, and fruit weight / hectare with a potential yield reached 7.25 tons / ha . Predictive value of genetic parameters of yield and yield component characters of melon plants showed that the coefficient of genetic diversity ( KKG ) criteria classified into low , whereas in the broad sense heritability classified into high criteria . Character crop yield and yield components of melon also showed predictive value of genetic correlations ranging from correlation is not real , very real to real . The character of the fruit weight is positive and highly significant correlation with the characters : ( 1 ) the largest fruit weight with r = 0.829 ** and ( 2 ) the weight of fresh fruit per acre with a value of r = 1.00 ** .